Dominant-negative constructs of human 6-phosphofructo-2-kinase/fructose-2,6-bisphosphatase-3 and -4: effect on the expression of endogenous 6-phosphofructo-2-kinase/fructose-2,6-bisphosphatase mRNA - Minchenko, D.O.; Bobarykina, A.Y.; Ratushna, O.O.; Marunych, R.Y.; Tsuchihara, K.; Moenner, M.; Caro, J.; Esumi, H.; Minchenko, O.H. (Біотехнологія, 2008)
Expression of 6-phosphofructo-2-kinase/fructose-2,6-bisphosphatase (PFKFB), a key regulatory enzyme of glycolysis, is significantly increased in different malignant tumors provides a potential mechanism of enhanced glycolysis and cancer cell proliferation. We created dominant-negative constructs of 6-phosphofructo-2-kinase/fructose-2,6-bisphosphatase-3 and -4 (dnPFKFB-3 and dnPFKFB-4) cDNA for suppression of strongly enhanced expression endogenous PFKFB-3 and PFKFB-4. We introduce point mutation in ATP-binding domain of 6-phosphofructo-2-kinase part of PFKFB-3 as well as PFKFB-4 cDNA for suppression of 6-phosphofructo-2-kinase activity in the products of dnPFKFB-3 and dnPFKFB-4 expression. Cancer cells were stable transfected with these dominant-negative constructs for suppression of endogenous PFKFB-3 and PFKFB-4 expression and cell proliferation. We have shown that PFKFB-3 expression in pancreatic cancer cell line Panc1, stable transfected by dnPFKFB-3, was significantly reduced in normal as well as in hypoxic conditions. Pancreatic cancer cells proliferation, stable transfected by dnPFKFB-3 or dnPFKFB-4, was also reduced. Results of this investigation demonstrate possibility to apply the dominant-negative constructs of PFKFB-3 and PFKFB-4 for suppression of glycolysis and tumor cells proliferation via reduction of endogenous PFKFB expression. Експресія 6-фосфофрукто-2-кінази/фруктозо-2,6-бісфосфатази (PFKFB), ключового регуляторного ензиму гліколізу, різко зростає в різних злоякісних пухлинах, що розкриває можливий механізм посиленого гліколізу в ракових клітинах та їх проліферації. Ми створили домінантнегативні конструкції кДНК 6-фосфофрукто-2-кінази/фруктозо-2,6-бісфосфатази-3 та -4 (dnPFKFB-3 та dnPFKFB-4) для пригнічення посиленої експресії ендогенних PFKFB-3 та PFKFB-4. Для цього вводили точкові мутації в АТР-зв’язувальний домен 6-фосфофрукто-2-кінази як PFKFB-3, так і PFKFB-4 кДНК для пригнічення 6-фосфо-фрукто-2-кіназної активності у продуктах експресії цих конструкцій. Проводили трансфекцію ракових клітин цими домінантнегативними конструкціями для пригнічення експресії ендогенних PFKFB-3 і PFKFB-4 та проліферації клітин. Встановлено, що експресія PFKFB-3 в клітинах карциноми підшлункової залози лінії Panc1, стабільно трансфекованих dnPFKFB-3, знижується як у нормальних умовах, так і за гіпоксії. У клітинах з посиленою експресією dnPFKFB-4 спостерігали пригнічення ендогенних як PFKFB-4, так і PFKFB-3. Проліферація клітин карциноми підшлункової залози, стабільно трансфекованих як dnPFKFB-3, так і dnPFKFB-4, знижується. Результати цих досліджень показують можливість використання домінантнегативних конструкцій PFKFB-3 та PFKFB-4 для зменшення інтенсивності гліколізу та проліферації ракових клітин шляхом зниження експресії ендогенних PFKFB. Экспрессия 6-фосфофрукто-2-киназы/фруктозо-2,6-бисфосфатазы (PFKFB), ключевого регуляторного энзима гликолиза, резко возрастает в различных злокачественных опухолях, что раскрывает возможный механизм усиленного гликолиза в раковых клетках и их пролиферации. Мы создали доминантнегативные конструкции кДНК 6-фосфофрукто-2-киназы/фруктозо-2,6-бисфосфатазы-3 и -4 (dnPFKFB-3 и dnPFKFB-4) для угнетения усиленной экспрессии эндогенных PFKFB-3 и PFKFB-4. Для этого вводили точечные мутации в АТР-связывающий домен 6-фосфофрукто-2-киназы как PFKFB-3, так и PFKFB-4 для угнетения 6-фосфофрукто-2-киназной активности в продуктах экспрессии этих конструкций. Проводили трансфекцию раковых клеток этими доминантнегативными конструкциями для угнетения экспрессии эндогенных PFKFB-3, а также пролиферации клеток. Установлено, что экспрессия PFKFB-3 в клетках карциномы поджелудочной железы линии Panc1, стабильно трансфецированных dnPFKFB-3, снижается как в нормальных условиях, так и при гипоксии. В клетках с усиленной экспрессией dnPFKFB-4 наблюдали угнетение эндогенных как PFKFB-4, так и PFKFB-3. Пролиферация клеток карциномы поджелудочной железы, стабильно трансфецированных как dnPFKFB-3, так и dnPFKFB-4, снижается. Результаты этих исследований показывают возможность использования доминантнегативных конструкций PFKFB-3 и PFKFB-4 для уменьшения интенсивности гликолиза и пролиферации раковых клеток путем снижения экспрессии эндогенных PFKFB.